Glycogen synthase 3 (GSK-3) regulation of PD-1 expression and and its therapeutic implications. (April 2019) - Krueger, Janna; Rudd, Christopher E.; Taylor, Alison
Abstract: The past few years have witnessed exciting progress in the application of immune check-point blockade (ICB) for the treatment of various human cancers. ICB was first used against cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) to demonstrate durable anti-tumor responses followed by ICB against programmed cell death-1 (PD-1) or its ligand, PD-L1. Present approaches involve the use of combinations of blocking antibodies against CTLA-4, PD-1 and other inhibitory receptors (IRs) such as TIM3, TIGIT and LAG3. Despite this success, most patients are not cured by ICB therapy and there are limitations to the use of antibodies including cost, tumor penetration, the accessibility of receptors, and clearance from the cell surface as well as inflammatory and autoimmune complications. Recently, we demonstrated that the down-regulation or inhibition of glycogen synthase kinase 3 (GSK-3) down-regulates PD-1 expression in infectious diseases and cancer (Taylor et al., 2016 Immunity 44, 274-86; 2018 Cancer Research 78, 706–717; Krueger and Rudd 2018 Immunity 46, 529–531). In this Review, we outline the use of small molecule inhibitors (SMIs) that target intracellular pathways for co-receptor blockade in cancer immunotherapy.